The Paralytic's Offering Worship and Disability - Volpe, Medi Ann 1969- (2018)
In this essay, the author argues that people with profound disabilities belong at the heart of our worshipping communities. Psalm 50 [49 LXX] offers us a different angle from which to consider the contribution of people who seem unable to participate in communal worship, and whose experience of God is beyond our perception. Applying the insights drawn from the psalm, the author turns to the narrative of Jesus' healing the paralytic, and argues that the same dynamic plays out in Mark's account of the episode. The contribution of people with profoundly limiting disabilities begins to emerge. The obvious need of the paralytic for the healing brought by Christ also draws his friends to Christ. The primary need of the paralytic is, as Christ shows, his need for forgiveness-a need shared by all present. This same dynamic, the author suggests, plays out in L'Arche communities: those who come as assistants discover their own need for God's love. The desire to help may have inspired the friends of the paralytic, but they are drawn into the space of revelation and forgiveness. Likewise, it was the cry for love that Jean Vanier heard, and to which he responded by forming the first L'Arche community. Those two disabled men brought Vanier closer to Jesus, and helped him create L'Arche.
Keywords: Down Syndrome; L'Arche; inclusive congregations; Intellectual disability; Suffering